The effect of giving cabbage litter on population growth of the african night crawder earthworm (Eudrilus eugeniae) - Melati, Puput; Karnan, Karnan; Merta, I Wayan (Jurnal Pijar Mipa, 2023)
Cabbage (Brassica oleracea) is one of the vegetable wastes that is often produced by the Amahami market, Bima City. With its easy-to-wilt nature and high water content, cabbage causes it to rot quickly, which will impact environmental problems. Processing market waste certainly requires sustainable management. One model of waste management is to use it as feed. This research aims to determine the effect of giving cabbage waste on the increase in the population of earthworms (Eudrilus eugeniae). The research was carried out in Bima City, Ule Village, Asakota District, Tolotongga Environment. The type of this research is experimental. The research design was a Completely Randomized Design (CRD) with four treatments and ten replications. The parameter observed was the increase in the number of earthworms, analyzed using One Way Anova and followed by Duncan's Multiple Range Test (DMRT). The results of the research showed that giving cabbage waste (Brassica oleracea) as feed had a significant effect (0.009<0.05) on increasing the population of earthworms (Eudrilus eugeniae). The treatment with the highest results was P1 (50 grams of cabbage), with an average number of worms of 367.30.